Lipid recovery from microalgae biomass using sugaring-out extraction in liquid biphasic flotation system - Aron, Nurul Syahirah Mat (2023)
The increase in global temperature calls for ambitious action to reduce the release of greenhouse gases into the atmosphere. The transportation sector contributes up to 25% of the total emissions released, mainly from the burning of vehicle fuel. Therefore, scientists from all around the world are focusing on finding a sustainable alternative to conventional vehicle fuel. Biofuel has attracted much attention, as it shows great potential for the replacement of traditional fossil fuels. However, the main bottlenecks of biofuel are the ongoing controversial conflict between food security with biofuel production. Therefore, this study focuses on a sustainable extraction of lipids from microalgae for the production of biofuel using a liquid biphasic flotation system coupled with sugaring-out method. This is the first study to combine the methods of liquid biphasic flotation system with the sugaring-out technique. It represents a holistic study of optimum and effective conditions needed to extract lipids from the system and to understand the reliability of sugar solution as the agent of cell disruption. At the 15-min flotation time, 150 g/L of fructose solution with a 1:2 mass separating agent-acetonitrile ratio successfully extracted up to 74% of lipid from Chlorella sorokiniana CY-1. Two types of fatty acid methyl esters were recovered from the study, with C5:0 being the main component extracted.